Prolonged Hypophosphatemia and Intensive Care After Curative Surgery of Tumor Induced Osteomalacia: A Case Report - Ryhänen, Eeva M.; Schalin-Jäntti, Camilla; Matikainen, Niina (Frontiers in Endocrinology, 2021)
Introduction Rare FGF23-producing mesenchymal tumors lead to paraneoplastic tumor-induced osteomalacia (TIO) presenting with phosphate wasting, hypophosphatemia, chronic hypomineralization of the bone, fragility fractures and muscle weakness. Diagnosis of TIO requires exclusion of other etiologies and careful search for a mesenchymal tumor that often is very small and can appear anywhere in the body. Surgical removal of the tumor is the only definitive treatment of TIO. Surgical complications due to chronic hypophosphatemia are not well recognized. Case Description The current case describes severe fragility fractures in a 58-year-old woman, who lost her ability to walk and was bedridden for two years. First, the initial diagnostic laboratory work-up did not include serum phosphorus measurements, second, the suspicion of adverse effects of pioglitazone as an underlying cause delayed correct diagnosis for at least two years. After biochemical discovery of hyperphosphaturic hypophosphatemia at a tertiary referral centre, a FGF23-producing tumor of the mandible was discovered on physical examination, and then surgically removed. Postoperatively, severe hypophosphatemia and muscle weakness prolonged the need for ventilation support, intensive care and phosphate supplementation. After two years of rehabilitation, the patient was able to walk short distances. The tumor has not recurred, and serum phosphate concentration has remained within normal limits during 3.5 years of follow-up. Conclusions The case report illustrates knowledge gaps in the diagnostic work-up of rare causes of low bone mass and fragility fractures. Compared to other low phosphate conditions, surgical recovery from TIO-induced hypophosphatemia warrants special attention. Increased alkaline phosphatase concentration may indicate impaired postsurgical recovery due to prolonged hypophosphatemia, underlining the need for proactive perioperative correction of hypophosphatemia.